Dissecting Sholl Analysis into Its Functional Components - Alex D. Bird; Hermann Cuntz (Cell Reports, 2019)
Summary: Sholl analysis has been an important technique in dendritic anatomy for more than 60 years. The Sholl intersection profile is obtained by counting the number of dendritic branches at a given distance from the soma and is a key measure of dendritic complexity; it has applications from evaluating the changes in structure induced by pathologies to estimating the expected number of anatomical synaptic contacts. We find that the Sholl intersection profiles of most neurons can be reproduced from three basic, functional measures: the domain spanned by the dendritic arbor, the total length of the dendrite, and the angular distribution of how far dendritic segments deviate from a direct path to the soma (i.e., the root angle distribution). The first two measures are determined by axon location and hence microcircuit structure; the third arises from optimal wiring and represents a branching statistic estimating the need for conduction speed in a neuron. : Bird and Cuntz show how Sholl analysis, a one-dimensional representation of a dendritic tree, can be reproduced from three basic properties of a neuron that define its connectivity, density of synaptic inputs, and balance between material and signal delay costs, thus linking an intuitive and accessible neuronal representation with function. Keywords: Sholl analysis, root angle, dendrite, morphology, connectivity